Analysis of Early Childhood Education Curriculum in Jember Regency and the Relevance of Multiple Intelligence-based Curriculum Development in the Era of “Merdeka Belajar” - LuhPutu Indah Budyawati; Yuniarta Syarifatul Umami (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2022)
The curriculum is one of the factors that influence the success of learning in early childhood education.